Colorectal Polyposis and Immune-Based Therapies - Pearl Jacobson-Brown; Manuela G Neuman (Canadian Journal of Gastroenterology)
The progression from precancerous (adenomatous) colon polyps to malignant colorectal cancer involves the complex actions of various cytokines on T cell proliferation, cell-cell adhesion, apoptosis and host immunity. A broad spectrum of new treatments, including innovative molecular therapies such as gene therapy and treatment with cytokines, is under experimental and preclinical investigation. Nonsteroidal anti-inflammatory drugs and selective cyclooxygenase-2 inhibitors have traditionally been used as inflammation-reducing agents in cases of colon adenoma. Currently, adjuvant immunotherapies such as recombinant gene therapy and antibody-cytokine fusion proteins are assuming a more significant role in the management of colorectal neoplasia. Furthermore, advances in antitumour necrosis factor antibodies for the treatment of ulcerative colitis and Crohn's disease may have potential as chemoprotective agents for the treatment of colon polyposis. The present review aims to discuss the immunological mechanisms underlying colon tumour progression and the molecular and immune-based therapies that are leading to new methods of prognosis and treatment.